Evaluation of Dimensional Stability, Accuracy and Surface Hardness of Interocclusal Recording Materials at Various Time Intervals: An In Vitro Study - Anup, G. (Springer-Verlag, 2011)
To evaluate and compare the dimensional stability, accuracy and surface hardness of three interocclusal recording materials at various time intervals. Polyvinylsiloxane, Zinc oxide eugenol, Aluwax were taken for this study. A stainless steel die of ADA specification no 19. was prepared. A total of ten samples were made with each group. The samples were measured using a travelling microscope of 10× magnification at 1, 24, 48 and 72 h time intervals. Five readings were taken for each sample, the mean was considered to measure the dimensional change, accuracy and surface hardness. The values obtained were statistically analysed by ANOVA and Tukey HSD-Honestly significant difference. Polyvinylsiloxane was the most dimensionally stable, accurate and had the highest surface hardness among the three inter-occlusal materials.